Quantum enhanced multiple-phase estimation with multi-mode N00N states - Hong, Seongjin; ur Rehman, Junaid; Kim, Yong-Su; Cho, Young-Wook; Lee, Seung-Woo; Jung, Hojoong; Moon, Sung; Han, Sang-Wook; Lim, Hyang-Tag (Nature communications, 2021)
Quantum metrology can achieve enhanced sensitivity for estimating unknown parameters beyond the standard quantum limit. Recently, multiple-phase estimation exploiting quantum resources has attracted intensive interest for its applications in quantum imaging and sensor networks. For multiple-phase estimation, the amount of enhanced sensitivity is dependent on quantum probe states, and multi-mode N 00 N states are known to be a key resource for this. However, its experimental demonstration has been missing so far since generating such states is highly challenging. Here, we report generation of multi-mode N 00 N states and experimental demonstration of quantum enhanced multiple-phase estimation using the multi-mode N 00 N states. In particular, we show that the quantum Cramer-Rao bound can be saturated using our two-photon four-mode N 00 N state and measurement scheme using a 4 × 4 multi-mode beam splitter. Our multiple-phase estimation strategy provides a faithful platform to investigate multiple parameter estimation scenarios. N00N states are a key resource in quantum metrology, but the use of their multi-mode extension for multiparameter estimation has been elusive so far. Here, the authors use multi-mode N00N states - with N=2 photons in 4 modes - for multiple-phase estimation saturating the quantum Cramer-Rao bound.